Pengaruh Kepemimpinan Dan Motivasi Terhadap Kinerja Karyawan Hotel Bintang Tiga Di Bandung Utara - Tia Listiaty; Sri Marini (Akademi Pariwisata NHI Bandung, 2021)
The purpose of this study was to obtain empirical evidence about the influence of leadership and motivation to performance of hotel employee in north Bandung. The results are expected to contribute in the development of human resources management for the company as weel as of the practitioners. The study was conducted at Hotel Ardan, Hotel Nalendra dan Hotel Isola. This study used survey method with quantitative research approaches. While the type of research in the form Descriptive Research and Verificative Explanation Research with time horizon in the form of cross-sectional data that reflect a picture of a situation at a particular time. To test the hypothesis of the study use statistical method of path analysis. Based on the result of calculations using extensions of the multiple regression analysis the result obtained are Y = 0,698X1 + 0,200X2 + ε1, from the equation the calculation result are obtained 0,070 and the determinant coefficient of 70%. The test results of research found a significant relationship between leadership and motivation to employee performance either simultaneously or partially. Keywords: Leadership, Motivation and performance employee.